Practical Considerations and Testing Nuances for the Detection of Lupus Anticoagulant: Do Low Phospholipid Screen Results, Assay Type, and Test Ratio Matter?. Issue 6 (2nd June 2021) - Asakrah, Saja; Davis, Roger; Bhargava, Parul
Abstract: Objectives: Lupus anticoagulant (LA) detection requires (1) prolongation of a phospholipid (PL)–dependent clot-based screening assay, (2) noncorrection upon adding normal pooled plasma, and (3) a confirmatory PL dependency test. Paired LA assays run screening and confirmatory tests simultaneously, with their test ratio (TR) or differences used to evaluate test results. We evaluated patients whose paired testing demonstrated PL dependence suggestive of LA, yet the low PL screen was not prolonged. Methods: Clinical and laboratory parameters are compared across (1) true positive (screen prolonged, TR positive) vs borderline (screen not prolonged, TR positive); (2) low-, moderate-, and high-TR subgroups; and (3) dilute Russell viper venom time (dRVVT) vs silica clotting time (SCT). Results: Borderline samples are not statistically different from true positives in their rate of repeat LA positivity or association with other anti-PL antibodies. Compared with true positives, borderline dRVVT is more frequent in pregnancy, women, and younger age. Elevated activated partial thromboplastin time is more frequent in true-positive dRVVT and SCT vs borderline and with an increasing dRVVT TR. LA persistence is more frequent with an increasing SCT TR. In addition, dRVVT true positivity is more frequent with thromboembolic events, while SCT is more frequent with autoimmunity and pregnancy complications. Conclusions: Negative low-PL screens may not necessarily lack LA. A reevaluation of the laboratory criteria for LA detection may be needed.